Signal parameter estimation in radio electronic systems - Литвин-Попович, Андрій Ігорович (Technology audit and production reserves, 2012)
The article describes results of a signal parameter estimation research for radio electronic systems, with emphasis given to remote sensing systems. Comparative analysis of signal parameter estimation methods has been provide